Study on the Utilization of Itchy Leaf Plants (laportea sp.) By the Community of Bariat Village, Konda District South Sorong Regency - Irnawati Irnawati; Mira Herawati Soekamto; Nur Hidaya (Median : Jurnal Ilmu Ilmu Eksakta, 2023)
Itchy leaves are a kind of herbaceous plant that comes from the Urticaceae family where if applied all over the body it will cause a very itchy effect. After the itchy sensation for 5 minutes, the pain and sore effects will work very effectively. The local Papuan people, especially the South Sorong area, are active in using itchy leaves as an effective traditional medicine to cure muscle pain, but until now it has not been known to identify the types of itchy leaves used by local people. This research examines the identification of the types of itchy leaves plants used. The methods used as aspects of the utilization of Itchy Leaf plants are observation, interviews, and filling out questionnaires. While the results of the study showed that there were three types of Itchy Leaf plants in Bariat Village, Konda District which belonged to 1 (one) family, namely Urticaceae. There are 3 types of itchy leaves, namely Laportea decumana (kafa'), Laportea stimulants syn (kafasa), and Laportea peltata (Kafa'). Furthermore, this group of Itchy Leaf plants is used by the community by rubbing, squeezing the leaves, wrapping and as a trap for wild animals.